ANALYSIS OF YIELD AND YIELD RELATED TRAITS VARIABILITY OF WINTER WHEAT (TRITICUM AESTIVUM L.) CV. IZOLDA AND DOUBLE HAPLOID LINES - Kozdój, Janusz; Mańkowski, Dariusz R.; Godzina-Sawczuk, Monika; Czaplicki, Andrzej (Plant Breeding and Seed Science, 2015)
The yield-forming potential of winter wheat is determined by several factors, namely total number of shoots per plant and total number of spikelets per spike. The field experiments were conducted during three vegetation seasons at the Plant Breeding and Acclimatization Institute – National Research Institute (PBAI– NRI), located in Radzików, Poland. The objective of this study was a comparative analysis of the structural yield-forming factor levels, which determine grain yield per spike and per plant of the DH lines and standard Izolda cultivar. Results indicate that several DH lines showed some differences in tested morphological structures of plant, yield factor levels and in grain yield per spike and per plant in comparison to standard Izolda, regardless of the year. Mean grain yield per plant of DH lines was 26.5% lower in comparison to standard Izolda only in the second year of study. It was caused by a reduction of productive tillers number. Structural yield-forming potential of DH lines was used in 38% and 59% and in case of Izolda in 47% and 61% (the second and the third year of experiment, respectively). The mean grain yield per spike of DH lines was 14.8% lower than Izolda cultivar only in third year of experiment and it was caused by about 12% lower number of grains per spike. Structural yield-forming potential of DH spikes was used in 82.4%, 85.4% and 84.9% and in case of Izolda in 83.8%, 87% and 89.5% (the first, the second and the third year of experiment, respectively). The grain yield per winter wheat plant (both DH lines and standard Izolda) was significantly correlated with the number of productive tillers per plant (r = 0.80). The grain yield per winter wheat spike (both DH lines and Izolda cultivar) was significantly and highly correlated with the number of grains per spike (r = 0.96), number of fertile spikelets per spike (r = 0.87) and the spike length (r = 0.80). Variation of spike and plant structural yield-forming factors determining grain yield levels were also analyzed. Calculated total variation coefficients values of each analyzed trait during three-year long studies were different depending on plant material – DH lines or standard Izolda. Low variation coefficients values characterized following traits (traits ranked by increasing values for DH lines and standard Izolda, respectively): total spikelets number per spike (6.6 and 6.3%), spike length (11.1 and 12.6%), fertile spikelets number per spike (13.7 and 11.7%), single grain weight (15.0 and 12.2%), shoot length (16.2 and 13.3%), grains number per spikelet (26.4 and 23.3%), total shoots number per plant (23.4 and 29.6%), grains number per spike (30.1 and 28.2%). Higher variation coefficients values were obtained for the following traits: grain yield per spike (40.0 and 35.7%), plant immature tillers number (35.8 and 42.6%), plant productive tillers number (42.2 and 43.2%), spike sterile spikelets number (46.6 and 44.7%) and number of grains per plant (58.3 and 60.5%). The highest values characterized grain yield per plant (66.9 and 60.8%).